Eficácia do hidroxinaftoato de befênio na Ancieostomose canina - Beck, A. A. H.; Boelter, R.; Beck, A. A. (Revista do Centro de Ciências Rurais, 2007)
Os autores estudaram a ação do hidroxinaftoato de befênio em caninos, na dose de 200 mg/kg de pêso vivo, na redução da ovopostura e eficácia nas formas adultas de Ancylostoma caninum, obtendo respectivamente 99,09% e 95,84 de eficácia do antihelmíntico.SUMMARYThe authors were studied the action of hydroxynaphthoate bephenium in dogs, dosage of 200 mg/kg body weight, in the reduction of eggs outputt efficacy of adults worrns Ancylostoma caninum, obtained respectvely 99,09 % , 95,84 of anthelrnintcs efficacy.